The horizontal and vertical components of nystagmus evoked by the supine roll test in horizontal semicircular canal canalolithiasis - Zhang, Xueqing; Deng, Qiaomei; Liu, Qiang; Wen, Chao; Wang, Wei; Chen, Taisheng (Frontiers in Neuroscience, 2022)
Objective The characteristics of horizontal and vertical components of nystagmus in patients with horizontal semicircular canal canalolithiasis (HSC-Can) were analyzed, according to Ewald's first law. It is provided a basis for the study of human horizontal semicircular canal function and structure, objective diagnosis and treatment of BPPV. Methods The records of patients that had been tested with 2-dimensional video nystagmography (2D-VNG) were reviewed, between June 2019 and June 2021. The intensity and direction of horizontal and vertical nystagmus elicited by supine roll test were analyzed in 189 patients with idiopathic HSC-Can. Results All 189 HSC-Can patients were induced horizontal nystagmus with the same direction as head-turning (geotropic) in the supine roll test, of which 119 patients (63.96%) had a weak vertical upward component of nystagmus on the affected and unaffected side, 57 patients (30.16%) had a vertical downward component on the affected side and/or the unaffected side, and 13 patients (6.88%) had no vertical component on both sides. The intensity values of the horizontal component on the affected and unaffected sides were 42.14±24.78°/s (range, 6.26-138.00°/s) and 17.48±10.91°/s (range, 2.40-53.83°/s), with a ratio of (2.96±2.17) :1, representing a significant difference (p < 0.0001). We analyzed the characteristics of horizontal and vertical components in 119 HSC-Can patients (57 L-HSC-Can and 62 R-HSC-Can) on the supine roll test. The intensity values of the horizontal component on the affected and unaffected sides were 43.17±23.76°/s (range: 8.60–124.51°/s) and 17.98±10.99°/s (range: 2.40–53.83°/s), and for vertical component were 10.65±8.46°/s (range: 1.90–50.83°/s) and 4.81±3.45°/s (range: 0.30–20.43°/s), representing a significant difference between groups (p < 0.001). We compared the horizontal and vertical components of nystagmus induced on affected and unaffected sides in supine roll test in 53 patients with normal UW and 51 patients with abnormal UW, and the difference was not statistically significant. Conclusions There is mostly a vertical upward component based on the horizontal component in HSC-Can, and the direction and intensity characteristics of nystagmus accord with Ewald's First law, which can provide a basis for the study of human HSC function and structure, objective diagnosis and treatment of BPPV.